Comparative Study of English and Uzbek Interrogative Pronouns and Sentences (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In modern linguistics in recent years, become a common trend in the study of syntax, including interrogative sentence as multidimensional syntactic unit. This makes it possible to consider the subject of study in its totality and diversity. Using this approach aims to study the functioning of proposals in the communication process. One of the main categories of communicative interaction is a category voprositelnosti constituting components of which are the interrogative sentences.